Consórcio de milho com forrageiras: atributos físicos do solo e produtividade - Santos, Paulo Ricardo Alves dos (2016)
The intensification of agricultural production systems is increasing in the current agriculture. In this sense, the simultaneous planting forage to grain crops, constitutes an alternative in the intensification of the production system, which can increase or not the productivity of the main crop, and produce straw for mulching. In order to check the occurrence of changes in the physical properties of the soil and in corn yield and dry matter production due to the corn consortium / forage in two sowing dates, this study was conducted in the experimental area of the Department of Agricultural Engineering of the Federal University of Ceará. The design was used in a randomized block design in a factorial scheme (3x2) + 1 with four replications, totaling 28 experimental units. The treatments consisted of three forages: Brachiaria, Panicum maximum cv. Mombaça and Crotalaria spectabilis intercropped with maize in two of fodder sowing dates, between the lines of simultaneous sowing maize (season 1 - E1) and corn leading the V4 stage of corn (season 2 - E2), and the control. The results showed that intercropping maize / forage did not interfere in phytotechnical characteristics of corn, nor in productivity, however produced changes in soil physical properties when the day of sowing in season 1. Despite the changes that have occurred in the soil, they were not sufficient to enhance the productivity of maize, which could possibly be related assessments on only one crop cycle. But when the goal was the production of dry straw, it is concluded that fodder Brachiaria brizantha and Mombasa at the time 1 (E1) are recommended